Fornecimento de água por meio de irrigação por aspersão para produção de sementes de arroz de terras altas - Crusciol, Carlos Alexandre Costa [UNESP]; Toledo, Mariana Zampar; Arf, Orivaldo [UNESP]; Cavariani, Cláudio [UNESP] (My University, 2012)
Physiological quality of rice seeds may be influenced by water deficiency at seed development and filling stages, which is often reported in upland cropping system. This study had the objective of evaluating the effects of sprinkler irrigation system on the improvement of physiological quality of rice seeds produced under upland conditions. wo experiments were carried out in Selvíria-S, Brazil, Ilha Solteira College of Engineering, UNESP, in 1994/1995 and 1995/1996, with the upland rice cultivars 'IAC 201' and 'Carajás'. In both years, rice plants were grown under rainfed and sprinkler-irrigation conditions. Based on the rice crop coefficient (Kc), the following water levels were obtained: L1: 0.5 times the Kc, L2: Kc, L3: 1.5 times the Kc, L4: Kc = 1.95. Weight, germination and vigor of rice seeds were evaluated right after harvest. The experimental design was the completely randomized with four replications. Data was submitted to analysis of variance and means were compared by Tukey's test (P≤0.05) separately for each cultivar. It was concluded that levels of water varying from 0.5 to 1.5 times the rice crop coefficient, supplied through sprinkler-irrigation system, provide better conditions to produce rice seeds of upland cultivars with higher physiological quality.
Water supplied by sprinkler irrigation system for upland rice seed production
Keywords: Germination; Oryza sativa; Rainfall; Vigor; Water availability